2018
DOI: 10.1021/acs.jafc.8b02115
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Tannin Fingerprints by Liquid Chromatography Tandem Mass Spectrometry Offer a New Dimension to Plant Tannin Analyses and Help To Visualize the Tannin Diversity in Plants

Abstract: Tannins are large-molecular-weight plant polyphenols that are produced in fruits, berries, leaves, flowers, seeds, stems, and roots of woody and non-woody plants. Hundreds and thousands of individual tannin structures are consequently found in many kinds of natural food and feed products. The huge structural variability in tannins is reflected as vast bioactivity differences between them but not in the accuracy of their typical analysis methods. Here, I show how the modern liquid chromatography mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“… 34 However, our results demonstrate that the mDP value does not describe the true DP distribution of PAs in tissue. Salminen 35 has already earlier remarked that the same mDP value can be achieved from PA profiles, which are completely unlike one another as it does not give information of the true size distribution of the PAs in a sample. Our results show that while the single numeric mDP value was fairly similar in all tissue samples, the MS/MS methods revealed that the true distribution of PC and PD terminal and extensions units varied markedly between the tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 34 However, our results demonstrate that the mDP value does not describe the true DP distribution of PAs in tissue. Salminen 35 has already earlier remarked that the same mDP value can be achieved from PA profiles, which are completely unlike one another as it does not give information of the true size distribution of the PAs in a sample. Our results show that while the single numeric mDP value was fairly similar in all tissue samples, the MS/MS methods revealed that the true distribution of PC and PD terminal and extensions units varied markedly between the tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the detailed PA fingerprints achieved by our MS/MS methods are extremely useful in accurately predicting bioactivities, as many of them are affected by the PC/PD ratio and the distribution of PAs of different degrees of polymerization, among other factors. 34 , 35 , 41 43 …”
Section: Discussionmentioning
confidence: 99%
“…The early‐eluting HHDP and galloyl derivatives eluted before oenothein B (0.5–2.9 min), and the late‐eluting ones were those from oenothein B onwards (2.9–6 min). Likewise, we re‐analysed the previously collected data to determine the concentration of procyanidins and prodelphinidins in each of the three size classes explained in Salminen (2018b). The smaller procyanidin and prodelphinidin oligomers were detected by cone voltages of 75 and 55 V, the medium procyanidin and prodelphinidin oligomers and polymers by cone voltages of 85 and 80 V, and the large procyanidin and prodelphinidin polymers by cone voltages of 140 and 130 V, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We anticipated that protein precipitation capacity would be positively correlated with the concentrations of proanthocyanidins (PAs; also known as condensed tannins), their mean degree of polymerisation (mDP) and the proportion of prodelphinidin subunits in PAs (Jones et al ., ; Porter & Woodruffe, ; McManus et al ., ; Aerts et al ., ). At a finer scale, we used the Engström method (Engström et al ., ) to measure PA concentrations at three cone voltages (see Salminen, 2018b), which provides additional information about the size distribution of PAs. We expected that large prodelphinidin‐rich PAs in particular would contribute positively to the protein precipitation capacity of samples, assuming that these types of PAs were in sufficient concentrations in the extracts.…”
Section: Introductionmentioning
confidence: 99%
“…Although NMR approaches are now being applied to PA analysis (Fryganas et al, 2018), they have yet to provide the structural resolution of similar approaches for the phenylpropanoid polymer lignin (Sette et al, 2011). Increasingly sophisticated mass spectrometry approaches are being applied to PA characterization (Salminen, 2018), but detailed structural features of the internal portions of polymers remain elusive.…”
Section: Phenotypes Of Tt Mutantsmentioning
confidence: 99%